Perceived Self-Efficacy among Special Education Students Enrolled in a Practical Training Program During the COVID-19 Pandemic in Jordan - Al-Taj, Heyam Musa (Journal of Ecohumanism, 2024)
The current study aimed to investigate the level of perceived self-efficacy among special education students enrolled in the practical training program during the COVID-19 pandemic in Jordan. The study sample consisted of (150) male and female students from various public and private Jordanian universities, who were purposefully chosen, and enrolled in practical training during the semesters that continued under the pandemic. To achieve the objectives of the study, the descriptive approach and the perceived self-efficacy scale prepared by the researcher were used. The results of the study showed that the level of perceived self-efficacy among students of practical training in the specialization of special education came at a high level; the results also indicated that the level of perceived self-efficacy concerning the employment of modern technology ranked first and at a high degree, while the self-efficacy related to teaching skills and behavior modification, as well as management, communication, and social responsibility came to a medium degree. The results also showed that there are statistically significant differences between the arithmetic averages of the level of perceived self-efficacy among students of field training in the specialization of special education who are registered in Jordanian universities according to the type of university (public/private) on the total degree and all dimensions except for the dimension (management, communication, and social responsibility) and in favor of private universities. The results also showed that there were statistically significant differences between the arithmetic averages of the level of self-efficacy among students of special education according to the type of training and its duration on the total degree and dimensions and in favor of the two training categories (full and continuous semester" and "full and intermittent semester"). In contrast, the results did not show any statistically significant differences between the arithmetic averages of the level of perceived self-efficacy among special education students enrolled in the practical training program during the COVID-19 pandemic in Jordan, according to the student’s gender.